Interpretation of the andean rural school in aimara communities of Puno-Perú - Bermejo-Paredes, Saúl (2019)
This article is an approximation to the ontological understanding of education from the indigenous-Aymara thinking. It is approached from the interpretative and contextual paradigm, basically using the hermeneutical method, aimed at the understanding and interpretation of the meaning that the community leaders and the Aymara population settled in the southern zone of Puno-Peru give to the school. The information was collected through documentary analysis, in-depth interviews marked by dialogical events that ensured equal interaction between the interlocutors, and based on the experience of shared life as Aymara people (between authors, authors and subjects of study). Through the process of re-interpretative analysis (interpretation of the interpretation), the gathered information has allowed establishing, as results of the study, that the presence of the Andean rural school, directed and administered by the Peruvian State, remains contrary to the sense given by the Aymara community to the expectations and experiences of particular life; it also remains as an excluding, vertical and rigid entity, as well as alien to the Aymara cosmovision. The study concludes that the epistemologies of hope have no place in Aymara thought; therefore, they do not want a school to stop being poor and marginalized in an uncertain time. According to the Aymara communities, the rural school should give meaning to life, enabling the full flowering of the being to live with dignity today, tomorrow and forever, in such a way that the school is not a hope of well-being, but rather the permanent emotional enjoyment (today) from which life is lived in harmony. This implies rethinking educational conceptions and policies from the State, ensuring a permanent process of openness and recognition of the ways of life and thought of indigenous populations.